2024
DOI: 10.3390/ma17030548
|View full text |Cite
|
Sign up to set email alerts
|

Cryogenic Treatment of Martensitic Steels: Microstructural Fundamentals and Implications for Mechanical Properties and Wear and Corrosion Performance

Peter Jurči,
Ivo Dlouhý

Abstract: Conventional heat treatment is not capable of converting a sufficient amount of retained austenite into martensite in high-carbon or high-carbon and high-alloyed iron alloys. Cryogenic treatment induces the following alterations in the microstructures: (i) a considerable reduction in the retained austenite amount, (ii) formation of refined martensite coupled with an increased number of lattice defects, such as dislocations and twins, (iii) changes in the precipitation kinetics of nano-sized transient carbides … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 306 publications
(1,098 reference statements)
0
5
0
Order By: Relevance
“…However, the 4%C-19%Cr-4%W alloy outperformed all the other alloys, with much lower carbide amounts despite comparable bulk hardness. Many examples of the beneficial effects of carbide phases have been reported in one of the most recent review papers [36]. At this place, it should be noted that, in 1994, Meng et al [37] observed that cryogenic treatments foster the precipitation of transient η-carbides at low tempering temperatures.…”
Section: Volume Loss (V)mentioning
confidence: 96%
“…However, the 4%C-19%Cr-4%W alloy outperformed all the other alloys, with much lower carbide amounts despite comparable bulk hardness. Many examples of the beneficial effects of carbide phases have been reported in one of the most recent review papers [36]. At this place, it should be noted that, in 1994, Meng et al [37] observed that cryogenic treatments foster the precipitation of transient η-carbides at low tempering temperatures.…”
Section: Volume Loss (V)mentioning
confidence: 96%
“…The benefits of low-temperature effects on the structural modification of metallic components have only been realized and exploited during the last 100 years and are a direct consequence of advances in science and technology that enable the creation of ultra-low-temperature environments [2]. Previous studies [3] have shown that such approaches were already attempted in the first half of the last century, whereby negative temperatures were used to improve the operational behavior of watch parts, engine blocks, military aircraft components, and chainsaw blade links. Liquefied carbon dioxide was used as a coolant in machine operations as early as 1919 [2].…”
Section: Introductionmentioning
confidence: 99%
“…Cryogenic is derived from the Greek word "κρ ύoς" meaning cold. Cryogenic conditions have a very wide range of applications in modern engineering: to improve the properties and operational behavior of steels (martensitic [3][4][5][6][7] and austenitic [8][9][10][11][12]) and non-ferrous alloys [13,14], workpieces [15], finished components [3] and tools [16][17][18], and as a cooling medium for machining [19][20][21][22] and plastic deformation [2]. It is, perhaps, for this reason of broad applicability that there is no consensus among researchers on temperature-based terminology.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations